2020
DOI: 10.3389/fncel.2020.00217
|View full text |Cite
|
Sign up to set email alerts
|

Otic Neurogenesis Is Regulated by TGFβ in a Senescence-Independent Manner

Abstract: Cellular senescence has classically been associated with aging. Intriguingly, recent studies have also unraveled key roles for senescence in embryonic development, regeneration, and reprogramming. Developmental senescence has been reported during embryonic development in different organisms and structures, such as the endolymphatic duct during inner ear development of mammals and birds. However, there is no study addressing the possible role of senescence on otic neurogenesis. TGFβ/SMAD is the best-known pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…The pattern of cell death in the developing avian heart also strongly correlates with SA-β-GAL staining ( Lorda-Díez et al, 2019 ), as do areas of cell death in the somites, tail bud, and CNS ( Muñoz-Espín et al, 2013 ; Storer et al, 2013 ). In the case of the developing otic vesicle in the chicken, SA-β-GAL labeled cells are associated with areas of increased apoptosis ( Figures 1A–C ) ( Gibaja et al, 2019 ; Magariños et al, 2020 ). In mice, it has been found that senescence in the endolymphatic sac has a morphogenetic role analogous to that of apoptosis ( Muñoz-Espín et al, 2013 ).…”
Section: Sa-β-gal Staining In the Developing Embryomentioning
confidence: 99%
“…The pattern of cell death in the developing avian heart also strongly correlates with SA-β-GAL staining ( Lorda-Díez et al, 2019 ), as do areas of cell death in the somites, tail bud, and CNS ( Muñoz-Espín et al, 2013 ; Storer et al, 2013 ). In the case of the developing otic vesicle in the chicken, SA-β-GAL labeled cells are associated with areas of increased apoptosis ( Figures 1A–C ) ( Gibaja et al, 2019 ; Magariños et al, 2020 ). In mice, it has been found that senescence in the endolymphatic sac has a morphogenetic role analogous to that of apoptosis ( Muñoz-Espín et al, 2013 ).…”
Section: Sa-β-gal Staining In the Developing Embryomentioning
confidence: 99%
“…We identified several mRNAs regulated by miR-21 that are likely to contribute to the regeneration of embryonic and adult tissues (including the endometrium) by promoting cell cycle quiescence, cell differentiation, migration, and/or angiogenesis [38][39][40][41][42]. Some have been also implicated in the reversal of cellular senescence [43][44][45], the attenuation of fibrosis [45,46] and the stress response [47,48]. Specifically, BDKRB1, a bradykinin G-coupled receptor B1, was significantly upregulated in eSFs by miR-21.…”
Section: Discussionmentioning
confidence: 99%